AFM contribution to unveil pro- and eukaryotic cell mechanical properties. (January 2018) - Kasas, S.; Stupar, P.; Dietler, G.
Abstract: Atomic force microscopy is nowadays a well-established technique that permits the investigation of numerous parameters of living matter. In particular, it allows the exploration of the mechanical properties of living organisms in almost physiological conditions. Here, we focus on the use of this technology to review recent contributions that relates the physiology and pathology of bacteria, yeast, plant and mammalian cells to their nano-mechanical properties.